Der Ausdruck von Emotionen und Bewertung durch Somatismen in einer Zeit der Krise - Perić Šormaz, Marija; Miletić, Nikolina (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
Body parts and their functions form a universal cognitive basis for the verbalization of psychological and physical concepts (Burger 2015:133). The term somatisms refers to phrasemes that contain a body part as a component. Body parts can stand for the whole person and evoke different emotions through various physical sensations (Buridant 2007: 1117). Linguistic expressions of emotions primarily serve an evaluative function (Fiehler 2010: 19). Evaluation refers to the speaker’s or author’s subjective stance, through which approval, disapproval, criticism, or endorsement is expressed (Martin/White 2005: 1). This analysis is based on a corpus of somatisms from the Croatian online newspaper “Večernji list” and the German online newspaper “Der Spiegel” from June 2022. This time period was chosen because the world was experiencing an intensifying crisis due to the war in Ukraine and rapid inflation. The study is conducted using the Appraisal Theory by Martin and White (2005) and its categories of affect and judgement. The analysis explores how somatisms in Croatian and German express emotions and evaluations. It determines which emotions (positive or negative) they convey and how people or situations are evaluated, for example, according to normality, capacity, tenacity, veracity or propriety.